ANALISIS PEMANFAATAN MATERIAL ALAM LOKAL SEBAGAI MATERIAL PERKERASAN JALAN DI PULAU MOROTAI, MALUKU UTARA: ANALYSIS OF THE USE OF LOCAL NATURAL MATERIALS AS ROAD PAVEMENT MATERIAL ON MOROTAI ISLAND, NORTH MALUKU - Eko Suyono; Jonbi (FTSP Universitas Jayabaya, 2021)
The construction of roads on Morotai Island is currently difficult to obtain standard materials and has always brought material from outside the island so that it will affect the cost of transporting/transport is quite high, and a long time. From some previous research that actually the material of stone and sand on Morotai Island is quite abundant, so it needs to be studied in order to be useful in the future. Results from research by testing materials from the Moloku, Libano and Gerong Rivers found that the material meets for the use of base A, B and S foundation layers and can save costs of up to 49%, with a saving of up to 15% of implementation time from plan time. While the quality for concrete mixture can be used up to the quality of fc'10, fc'15 and fc'25 according to the calculation of the thickness of rigid pavement can be used for road pavement in morotai island location with a thickness of 15 cm with a bone of Ø 8 distance of 150 mm.